Maleimide Containing UV-Cured Hybrid Coatings - OKTAY, BURCU; KAYAMAN APOHAN, NİLHAN (WILEY-HINDAWI, 2013)
In this work, new organic-inorganic hybrid coatings were prepared by the sol-gel method. N-p-hydroxyphenyl maleimide was synthesized and then modified with 3-isocyanato propyltriethoxysilane to obtain a new alkoxysilane monomer. Poly(dimethyl siloxane (PDMS) based on the urethane acrylate oligomer was synthesized using hydroxyl-terminated PDMS, isophorone diisocyanate, and 2-hydroxyethyl methacrylate. This oligomer was synthesized to increase the hydrophobicity of coatings. Hybrid formulations were applied onto polycarbonate plates and irradiated with UV light. Coatings' performance was investigated with thermal, mechanical, morphologic, and antibacterial analyses. It is observed that the thermal stability of UV-cured films is improved with the incorporation of the sol-gel precursor. It is shown that the nanosilver addition to hybrid coatings leads to significant enhancements in antibacterial property in vitro. (C) 2013 Wiley Periodicals, Inc.
Keywords: Coatings; Nanocomposites; Nanosilver; N-p-hydroxyphenyl maleimide; Photopolymerization; SILICA